2012
DOI: 10.2494/photopolymer.25.467
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Swelling Behavior of ArF Resist during Development by using QCM Method (2)

Abstract: Many reports have discussed the swelling behavior of photoresists during development, as observed by the QCM method. Previously, we reported on the development of development analysis equipment based on the QCM method. In this paper, we report on a high-precision resist development analyzer also based on the QCM method. This equipment incorporates a high-precision developing solution temperature controller and features a high-precision air conditioning function for the measurement chamber. We also measured swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many QCM studies of resist materials have been made and there is little evidence of swelling of PHS materials. Measuring initial responses on a QCM at a small fraction of a second is challenging due to an additional frequency shift caused by to the heat shock during the introduction of the solvent Sekiguch et al 19 . Horumoto et al 20 showed a thick transient swelling layer for acrylic resist while PHS showed little swelling.…”
Section: Solvent Penetration and Disentanglementmentioning
confidence: 99%
“…Many QCM studies of resist materials have been made and there is little evidence of swelling of PHS materials. Measuring initial responses on a QCM at a small fraction of a second is challenging due to an additional frequency shift caused by to the heat shock during the introduction of the solvent Sekiguch et al 19 . Horumoto et al 20 showed a thick transient swelling layer for acrylic resist while PHS showed little swelling.…”
Section: Solvent Penetration and Disentanglementmentioning
confidence: 99%
“…For example the quartz crystal microbalance (QCM) technique, 5 has been used to measure the dissolution response of photoresist exposed to clear-field or unpatterned radiation, showing a brief swelling of the resist before its rapid removal. 6 Similarly, Itani et al performed AFM experiments measuring the dissolution response of patterned resist materials, and also observed swelling prior to removal of the exposed material. 7 This swelling my be a significant contributor to LER, and has been cited as a motivating factor in the search for novel developers, including a tone-switch by using solvent developer 8 .…”
Section: Introductionmentioning
confidence: 99%